Hubungan Dukungan Keluarga dengan Perilaku Lansia dalam Pengendalian Hipertensi di Wilayah Puskesmas Fakfak Kota Kabupaten Fakfak - Ketut Wahyudi; Bachrudin Rohrohmana; Piere S. Kwando (Malahayati Nursing Journal, 2023)
ABSTRACT Support from family and friends is really needed by hypertension sufferers in controlling hypertension. The family becomes a support system in the lives of elderly people with hypertension, so that their condition does not continue to get worse and is free from complications due to hypertension. The aim of this research is to analyze the relationship between family support and elderly behavior in controlling hypertension in the Fakfak Community Health Center, Fakfak Regency. The research method used is analytical quantitative research with a cross sectional approach. The total sample was 111 people suffering from hypertension in the working area of the Fakfak Community Health Center. The results of the chi square test analysis with a significance level of 0.05% show that the p value is 0.000 0.05%, which means there is a significant relationship between family support and the behavior of the elderly in controlling hypertension in the working area of the Fakfak Community Health Center. To control hypertension, the elderly need family support which can then influence hypertension control behavior in the elderly. The advice given to families is that families hope to increase their support for elderly people who suffer from hypertension, so that the behavior of elderly people in controlling hypertension becomes better. Keywords: Family Support, Behavior, Elderly, Hypertension  ABSTRAK Support keluarga serta teman sangat dibutuhkan penderita hipertensi dalam pengendalian hipertensi. Keluarga menjadi support system dalam kehidupan lansia pengidap hipertensi, supaya kondisi yang dirasakan tidak terus menjadi memburuk serta bebas dari komplikasi akibat hipertensi. Tujuan penelitian ini adalah untuk menganalisis hubungan antara dukungan keluarga dengan perilaku lansia dalam pengendalian hipertensi di wilayah Puskesmas Fakfak Kota Kabupaten Fakfak. Metode Penelitian yang digunakan yaitu penelitian kuantitatif analitik dengan pendekatan cross sectional. Jumlah sampel sebanyak 111 orang penderita hipertensi di wilayah kerja Puskesmas Fakfak Kota. Hasil analisis uji chi square dengan taraf signifikan 0, 05% menunjukkan bahwa nilai p value 0, 000 0,05% yang artinya terdapat hubungan yang bermakna antara dukungan keluarga dengan perilaku lansia dalam pengendalian hipertensi di Wilayah kerja Puskesmas Fakfak Kota. Untuk mengendalikan hipertensi, lansia memerlukan dukungan keluarga yang kemudian dapat mempengaruhi perilaku pengendalian hipertensi pada lansia. Saran yang diberikan untuk keluarga diharapkan keluarga lebih meningkatkan dukungan terhadap lansia yang menderita hipertensi, agar perilaku lansia dalam pengendalian hipertensi menjadi lebih baik. Kata Kunci: Dukungan Keluarga, Perilaku, Lansia, Hipertensi